IMPLEMENTASI KEBIJAKAN PENERTIBAN IZIN HIBURAN BILLIARD DI KOTA PEKANBARU TAHUN 2010-2015 - Muhammad Yusuf; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The aims of this research to knew and analyze the implementation the policy of policing entertainment billiard permission in Pekanbaru City at 2010-2015. The phenomenon showed that still there is a company entertainment billiard that has the permission of operation still violate the operational time. Place that being location of this research is the office of Satpol PP, Dinas Kebudayaan and pariwisata pekanbaru city, and the place of entertainment billiard in Pekanbaru City. The informant of this research are they involved directly in the implementation policy include of Kepala Dinas Kebudayaan dan pariwisata, Seksi Rekreasi dan Hiburan Dinas Kebudayaan dan Pariwisata, Kepala Satpol PP, Sekretaris Satpol PP, Kepala Bidang Ketertiban Umum Satpol PP and aslo owner of Teratai Billiard Sport and Planet Billiard.According the result of this research showed a conclusion that implementation policy of the local government in policing the permission of entertainment billiard in Pekanbaru city that looked from the aspect of entertainment permission, the operational time, the sanctions and fine include of the supervision unoptimal yet. It can showed that the operational of entertainment billiard in Pekanbaru City still violate the provison such like the operatonal time of entertainment billiard and violate the standard not sell the liquor . The threat of implementation local government policy in policing permission of entertainment billiard in Pekanbaru City is clearly the planning is unoptimal yet, lack of Human Resources and weak of provision criminal inside of that policy. So that any of the weakness, will give big chance for actors that involved in implementation policy to policing permission of entertainment billiard to got the profit. So that’s the other effort to minimaze is supervision is not working as usual.Keywords: Implementation, Policy, Billiard Entertainment.